Flow and Heat Transfer Phenomena around an Equilateral Triangular Bluff Body: Effect of Wall Confinement. Issue 7 (4th April 2015) - Dhiman, Amit Kumar
Abstract : This paper focuses on the effects of wall confinements (or blockage ratios) on the flow and heat transfer characteristics around a long equilateral triangular bluff body placed in a horizontal channel for Reynolds number (Re) range 1 to 80 and blockage ratio range 0.1 to 0.5 for air as the working fluid. The governing continuity, Navier–Stokes and energy equations along with appropriate boundary conditions are solved by using a finite volume method‐based commercial solver Ansys Fluent. The total drag coefficient decreases with an increasing value of Re for a fixed value of the blockage ratio; however, it increases with an increasing value of the blockage ratio for a fixed value of Re due to the fact that the channel walls exert an extra retardation force on the obstacle. The onset of flow separation is delayed as the value of the blockage ratio increases. The critical Re (i.e., the transition to a time‐periodic regime) exists between 45 and 46, 46 and 47, 58 and 59, and 79 and 80 for the blockage ratios of 0.1, 0.125, 0.25, and 0.5, respectively. The simple correlations for wake length, total drag coefficient, and average obstacle Nusselt number are obtained for the range of conditions covered.